Detection of NO2 pollution plumes from individual ships with the TROPOMI/S5P satellite sensor. (4th December 2020) - Georgoulias, Aristeidis K; Boersma, K Folkert; van Vliet, Jasper; Zhang, Xiumei; van der A, Ronald; Zanis, Prodromos; de Laat, Jos
Abstract: This paper presents an analysis of tropospheric NO2 column measurements from the TROPOspheric Monitoring Instrument onboard the Copernicus Sentinel 5 Precursor satellite (TROPOMI/S5P) for an oceanic area in the central Mediterranean on 2 July 2018. The day and area were selected because of the stable and cloud-free weather conditions with low wind speeds throughout most of the area, while covering one of the busiest worldwide international shipping corridors. In addition, the area was affected by sunglint, i.e. sunlight that is directly reflected by the ocean surface waves to the satellite which greatly enhances the signal-to-noise ratio of the satellite observations. The satellite measurements reveal plume-like emission structures in tropospheric NO2 columns while automated identification signal (AIS) data of ship locations reveal a total of 185 ships in the area. Combined with information about wind speed and wind direction within 3 h prior to the TROPOMI/S5P overpass, the ship tracks can almost perfectly be aligned with the plume-like tropospheric NO2 structures. In addition, information about ship length and ship speed, combined with an analysis of ship tracks and ship position, reveal that nearly all emission plume-like tropospheric NO2 structures can be attributed to the largest ships, mostly container ships and crude oil tankers. Overall, our results show for the first time ever that NO2 emission plumes from ships can be detected and attributed to individual ships using satellite measurements, while also providing strong support for using satellite sunglint measurements.